2020
DOI: 10.1186/s12913-020-05429-6
|View full text |Cite
|
Sign up to set email alerts
|

Level of quality of option B+PMTCT service provision in public health facilities in Mekelle zone, northern Ethiopia: cross-sectional study

Abstract: Background: Substantial improvements have been observed in coverage and access to maternal health services in Ethiopia. However, the quality of care has been lagging behind. Therefore, this study aimed to assess the level of quality of Option B + PMTCT in Northern Ethiopia. Methods: A facility based survey was conducted from February to April 2016 in Northern Ethiopia. Twelve health facilities were enrolled in the study. Mixed method approach was used in line with Donabedian (Input-Process-Output) service qual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
(52 reference statements)
1
10
0
Order By: Relevance
“…This could be due to the fact that ongoing supervision and monitoring improve services quality if it is done countinously. This study finding is similar with the study done in Northern Ethiopia, Tigray and Amhara Region [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This could be due to the fact that ongoing supervision and monitoring improve services quality if it is done countinously. This study finding is similar with the study done in Northern Ethiopia, Tigray and Amhara Region [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…According to the above study, the overall level of service quality of Option B + PMTCT service was rendered as good in one out of six(16.7%) of the studied health facilities. In particular, 33.3 percent of health institutions reported good input service quality, but only 25 percent of them also reported good process and output service quality [ 17 ]. The limited sample size in our study may have contributed to this discrepancy because only four hospitals were studied in our study to evaluate the quality of option B + PMTCT services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25–27 Another qualitative study in northern Ethiopia showed about 33% of input, 25% of process, and output service quality. 28 Furthermore, a mixed-method study showed that the overall quality of PMTCT services was low (47%). 29 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the country has made strides at strengthening and expanding advanced neonatal care, neonatal intensive care unit (NICU), and Essential New-born Care (ENBC) services including services for low birth weight and preterm neonates [ 20 , 21 ]. On top of this, interventions such as introducing micronutrient supplementation as a maternal nutritional program [ 22 ], enhancing the quality of antenatal care [ 23 ], improving the management of sexually transmitted infections [ 24 ], and improving access to services aimed at preventing Mother to Child Transmission of HIV [ 25 ] and enhancing awareness on the utilization of insecticide-treated bed net during pregnancy [ 26 ] were taken as a specific measure to reduce the burden of stillbirth Ethiopia. Despite all these efforts, the reduction rate of perinatal mortality is not that satisfactory [ 27 ].…”
Section: Introductionmentioning
confidence: 99%